THE IMPACT OF DIGITAL PHOTOGRAPHY PROCESSING IN MOBILE APPLICATIONS ON THE QUALITY OF REACH IN SOCIAL MEDIA - Paśnikowska-Łukaszuk, Magdalena; Urzędowski, Arkadiusz (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2020)
Modern technologies allow for quick processing of digital images. In the era of the Internet, there are many mobile applications supporting the digital processing of photos used on social media. The algorithms of many popular social networks focus on many factors, however, the photography that is placed on a given portal is of great importance. Social media allows you to reach many sources and people. With the help of a good photo, we can get high post reach that contain additional information. The use of mobile applications helps to achieve very good results. This paper presents the results obtained in the process of comparing posts using digital photo processing with those in which the photos were used without processing in a graphics program.